Assessment Of Green Building Based On Greenship For New Building Version 1.2 Using Fuzzy Logic - Fajrin Nur Arlisyah; Sri Sukmawati; Anita Trisiana (Indonesian Society of Applied Science, 2020)
Green Building Council Indonesia (GBCI) is an institution established by building construction and construction sector professionals with a rating system for each building called Greenship. Greenship is a value as a benchmark of green building. One of the GBCI certifications is Greenship for new buildings. Jember University is a tertiary institution which has started to build high-rise buildings to provide facilities for the students. One of the multi-story buildings being built is the Postgraduate building for 5 (five) floors of law faculty students who completed their work in October 2019 so that the assessment is carried out until the Final Assessment stage. Using the assessment of Greenship for new buildings version 1.2 an assessment is carried out to determine the rating of the building. Assessment is done by direct observation, interviews, and questionnaires. The assessment results are processed using the fuzzy logic method through the Matlab application which refers to the Greenship guide for new buildings 1.2. After the assessment, the Postgraduate Faculty of Law building received a score of 40,6 (Bronze). Based on these results a recommendation is made so that it gets a value of 46,6 with a Silver rating.